(untitled) (Eurasian Journal of Ecology, 2019)
Abbreviations: CMC – carboxymethylcelllose; g/l – gram per liter. The aim this study was the isolation and characterization of thermophilic bacteria from geothermal hot spring in Zharkent town, Almaty region, Kazakhstan. Thermophilic bacteria are less studied but important group of microorganisms due to their ability to produce industrial enzymes. Eight bacterial isolates were characterized by morphological, microscopic, biochemical, and physiological characteristics. Eight bacterial isolates were isolated which capable growing at 81°C. The isolates were screened for amylase, protease, lipase and cellulose activity. The seven from eight isolates tentatively as Thermus sp. by morphology, biochemistry and physiological characteristics and one as Bacillus sp. The study confirmed that the isolates from geothermal hot spring Zharkent to be a true thermophile and could be a source of thermostable enzymes which can be exploited for industrial applications; four isolates (AW4, AW5, AW7, AW8) from eight showed good enzymatic characterization according to the results of their cultivations on solid medium. Isolation procedures were first carried out under various combinations of culture conditions; temperature (50, 60, 70, 80 and 90ºC), different media (for amylase, cellulase, lipase producer), various pH (5, 6, 7, 8 and 10). Results indicated a high phenotype diversity and hydrolase enzymes activity, which encourages future studies to explore further industrial and environmental applications. Key words: thermophiles, Zharkent geothermal hot spring, amylase, lipase, isolates